Penerapan Metode Muroja’ah Dan Sima’i Dalam Peningkatkan Hafalan Al Qur’an Siswa Di MA Al Washoya Kertorejo Ngoro Jombang - Khumairoh An Nahdliyah; Mar'atul Azizah; Farikhatul Ilmiyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
This study aims to describe the memorization ability of the Qur'an students at MA Al Washoya, application of the muroja'ah dani sima'i method in MA Al Washoya, what are the supporting and inhibiting factors in the application of the muroja'ah and sima'I methods in MA Al Washoya Kertorejo Ngoro Jombang. So the purpose of this study is to determine the memorization ability of the Qur'an students at MA al Washoya, the learning of tahfidz muroja'ah and sima'I methods at MA Al Washoya, as well as the supporting and inhibiting factors.This research uses a type of field research (field research) and uses a qualitative descriptive approach, the data collection techniques used are observation, interviews and documentation. For data analysis techniques, researchers use data reduction (explaining data), displaying (presenting data), drawing data (drawing conclusions). As a test of data validity, researchers use triangulation, which is checking data from various sources, methods, and times. The results of the study stated that: the implementation of Tahfidz learning the muroja'ah and sima'I methods at MA Al Washoya was taught 4 times a week in several stages, the stages of the muroja'ah method were: memorization, muroja'ah with friends, depositing memorization on the tahfidz teacher. The stages of the sima'I method are: listening to the recitation of the guru tahfidz, repeating by opening the Qur'an, repeating by closing the Qur'an. The supporting factors are self-motivation and closest people (family), the existence of guided muroja'ah activities, (sima'an), talents, appreciation given to outstanding students. Meanwhile, the inhibiting factors are the diverse abilities of students, the emergence of laziness, unhealthyness, the presence of tahfidz teachers because when the teacher is not present it will hinder the tahfidz learning process.